The Synergistic Relationship Between Corporate Communication and Crisis Management Practices - Edith Oghenechovwe OTUYA-ASOHRO (Journal of Communication and Public Relations, 2026)
This study examines the strategic role of corporate communication in crisis management through a systematic literature review (SLR) of peer-reviewed journal articles published between 2015 and 2025. Although the interrelationship between corporate communication and crisis communication has been widely acknowledged, existing scholarship remains fragmented in explaining how corporate communication operates as a governance mechanism during crises, particularly within the framework of Situational Crisis Communication Theory (SCCT). Using a systematic review approach, this study analyzed 42 peer-reviewed articles indexed in Scopus, Web of Science, and Google Scholar that explicitly addressed corporate communication, crisis communication, reputation management, and SCCT. The findings reveal three dominant patterns: (1) a shift from reactive message control to dialogic, transparent, and ethical communication practices; (2) the institutionalization of corporate communication as a core crisis governance function rather than a support activity; and (3) the increasing influence of digital media and stakeholder-driven narratives on crisis outcomes. This study contributes a synthesized conceptual framework that positions corporate communication as a strategic integrator aligning crisis response, stakeholder expectations, and reputational recovery. By reframing SCCT from a message-selection model into a communication capability perspective, this review offers theoretical enrichment and practical implications for organizations operating in digitally accelerated crisis environments.